Correction: EPR detection and characterisation of a paramagnetic Mo(iii) dihydride intermediate involved in electrocatalytic hydrogen evolution. Issue 16 (12th April 2016) - Prior, Christopher; Webster, Lee R.; Ibrahim, Saad K.; Wright, Joseph A.; Alghamdi, Ali F.; Oganesyan, Vasily S.; Pickett, Christopher J.
Abstract : Correction for 'EPR detection and characterisation of a paramagnetic Mo(iii ) dihydride intermediate involved in electrocatalytic hydrogen evolution' by Christopher Prior, et al., Dalton Trans., 2016, 45, 2399–2403.